Antimicrobial, Antifungal, Antioxidant Activity and Phytochemical Investigation of Phenolcarboxylic Acids by GC-MS of Raspberry (Rubus idaeus L.) Shoot Lipophilic Extract - Maslov O.; Komisarenko M.; Ponomarenko S.; Kolisnyk S.; Osolodchenko T.; Golik M. (Sciendo, 2024)
To determine the content of phenolcarboxylic acids using gas chromatography-mass spectrometer (GC-MS) in the obtained extract, conduct a study of the antimicrobial, antifungal, and antioxidant activities of Rubus idaeus shoot lipophilic extract.